Crop Production Management for Sustainable Agriculture: A Study in Angul District of Odisha - Samant, Tiryak Kumar (International Journal For Research In Agricultural And Food Science, 2017)
The study was carried out to know the influence of crop crop management for sustainable agriculture in Angul district of Odisha in India. The study indicates that crop production depends on the successful implementation of the soil, water, and nutrient management technologies.Sustainable agriculture integrates three main goals — environmental health, economic profitability, and social and economic equity. Different strategies like natural resources management, increasing Agricultural inputs use efficiency, sustainability of crop production resource base could be done for efficient crop production management. Thus, Krishi Vigyan Kendra had taken different steps through on farm testing and front line demonstration for horizontal spread of different varieties, technologies in crop production.